Association of Lipid Profile with fasting and Post Prandial Glucose Level in type 2 Diabetic Patients - Jayan, Archana; Dubey, Raju Kumar; Padmavati, P; Jha, Amit Chandra; Gautam, Narayan (Journal of Universal College of Medical Sciences, 2015)
INTRODUCTION: The cardiovascular disease (CVD) is associated with diabetes mellitus and dyslipidemia plays important role in CVD. This paper explores the frequency and pattern of dyslipidemia in type 2 diabetes mellitus patients and that compared with healthy control. The correlation of glucose level with lipid profile including Non-HDL/HDL and TG/HDL has been projected in this study. MATERIAL AND METHODS: This case-control study includes 263 type 2 diabetes mellitus and compared with 55 healthy controls. The diagnosis of Diabetes mellitus was made according to the World Health Organization (WHO) criteria and the criteria for dyslipidemia was obtained by National Cholesterol Education Program Expert Panel/American Treatment Protocol III (NCEP/ATP III). RESULTS: Most common dyslipidemia was found in increase TG (49.42%) followed by decreased HDL (48.66%), increased LDL (40.30%) and increased TC (33.84%) respectively. The proportion is much higher in male than female. The statistically significant differences between control and case for glucose and lipid profile were observed in FBS (p < 0.001), PPBS (p < 0.001), HDL (p < 0.01), Non-HDL/HDL (p < 0.002) and TG/HDL (p < 0.039). TG, TC and LDL were statistically non- significant between control and case. The Pearson's correlation coefficient shows significant correlation of FBS and PPBS with TG (p < 0.01), Non-HDL/HDL (p < 0.01) and TG/HDL (p < 0.01) respectively. CONCLUSION: Our study has suggested the dyslipidemia is associated with DM with increased TG, low HDL, high cholesterol and LDL. The increased Non-HDL/HDL and TG/HDL could be better indicator than single lipid abnormality which needs to be verified prospectively by including large population and controls Journal of Universal College of Medical Sciences Vol. 3, No. 1, 2015: 2-5